(untitled) (Boston, 1999)
PRINCIPLES OF ACCOUNTING continues to lead the market with balanced, flexible content supported by an array of integrated print and technology supplements. Designed for both majors and non-majors, the new edition focuses on the relevance of accounting in business with an emphasis on decision-making and analysis. Whether an instructor wants to present a user or procedural orientation, incorporate new instructional strategies, develop students' core competencies, or integrate the latest technology into the classroom, the 2005e Edition provides a total solution. The integrated text and technology program engages students in relevant issues and themes, from the Enron crisis--which led to a series of amendments in accounting law--to the controversy surrounding stock options. Case studies, accompanied by provocative questions, help build critical thinking skills and connect accounting to the real world of business.
Keywords: Kế toán,Accounting